2006
DOI: 10.1089/vbz.2006.6.216
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Diterpenes from Pterodon polygalaeflorus

Abstract: Ethanolic extract from seeds of Pterodon polygalaeflorus (Benth) has been shown to possess significant larvicidal activity against the mosquito Aedes aegypti. Bioassay-guided fractionation of the extract led to the isolation and characterization of the know diterpenoid furans 6alpha-hydroxyvouacapan-7beta,17beta-lactone (1), 6alpha,7beta-dihydroxyvouacapan- 17beta-oic acid (2) and methyl 6alpha,7beta-dihydroxyvouacapan-17beta-oate (3). The structures were established from infrared (IR), ultraviolet (UV), 1H-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 11 publications
0
19
0
6
Order By: Relevance
“…Higher percentages of mortality were observed at higher concentrations of the isolated compound. Earlier report showed that the compounds like diterpenoid furans 6alpha-hydroxyvouacapan-7beta, 17beta-lactone (1), 6al-pha, 7beta-dihydroxyvouacapan-17beta-oic acid (2) and methyl 6alpha, 7beta-dihydroxyvouacapan-17beta-oate (3) from seeds of Pterodon spolygalaeflorus exhibited LC 50 values of 50.08, 14.69 and 21.76 microg/ml against fourthinstar A. aegypti larvae, respectively (Omena et al 2006). Siddiqui et al (2004) have reported that the compounds spipnoohine (1) and pipyahyine (2) isolated from the petroleum ether extract of dried ground whole fruits of V Variance of estimated log lethal dose; SE standard error; LC 50 lethal concentration that kills 50% of the exposed larvae; LC 90 lethal concentration that kills 90% of the exposed larvae; LL lower limit (95% confidence limit); UL upper limit (95% confidence limit); C x mean of Piper nigrum exhibited toxicity at 35.0 and 30.0 ppm, respectively, against fourth-instar larvae of A. aegypti.…”
Section: Resultsmentioning
confidence: 99%
“…Higher percentages of mortality were observed at higher concentrations of the isolated compound. Earlier report showed that the compounds like diterpenoid furans 6alpha-hydroxyvouacapan-7beta, 17beta-lactone (1), 6al-pha, 7beta-dihydroxyvouacapan-17beta-oic acid (2) and methyl 6alpha, 7beta-dihydroxyvouacapan-17beta-oate (3) from seeds of Pterodon spolygalaeflorus exhibited LC 50 values of 50.08, 14.69 and 21.76 microg/ml against fourthinstar A. aegypti larvae, respectively (Omena et al 2006). Siddiqui et al (2004) have reported that the compounds spipnoohine (1) and pipyahyine (2) isolated from the petroleum ether extract of dried ground whole fruits of V Variance of estimated log lethal dose; SE standard error; LC 50 lethal concentration that kills 50% of the exposed larvae; LC 90 lethal concentration that kills 90% of the exposed larvae; LL lower limit (95% confidence limit); UL upper limit (95% confidence limit); C x mean of Piper nigrum exhibited toxicity at 35.0 and 30.0 ppm, respectively, against fourth-instar larvae of A. aegypti.…”
Section: Resultsmentioning
confidence: 99%
“…Secretory structures on the pericarp of P. emarginatus produce and accumulate resinous terpene-based substances, especially diterpenes (Fascio et al 1976) which demonstrate biological activity as cercaricides (Mors et al 1966) and larvicides (De Omena et al 2006), and are used for various purposes in folk medicine (Almeida et al 1998, Teixeira et al 2001). According to Almeida et al (1998), the winged endocarp is rich in extremely aromatic essential oils that are used to treat rheumatism and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The control Rodrigues et al, 2005). Earlier authors reported that the larvicidal activity of isolated compound from Magonia pubescens with LC 50 value of 3.1 ppm against Aedes aegypti larvae (Silva et al, 2004); similarly the isolated compounds like diterpenoid furans 6alpha-hydroxyvouacapan-7beta, 17beta-lactone (1), 6alpha, 7beta-dihydroxyvouacapan17beta-oic acid (2) and methyl 6alpha, 7beta-dihydroxyvouacapan-17beta-oate (3) from seeds of Pterodon spolygalaeflorus exhibited LC 50 values of 50.08, 14.69 and 21.76 μg/mL against fourth-instar Aedes aegypti larvae, respectively (De Omena et al, 2006); Siddiqui et al (2004) reported that the compounds spipnoohine (1) and pipyahyine (2) isolated from the petroleum ether extract of dried ground whole fruits of Piper nigrum exhibited toxicity at 35.0 and 30.0 ppm respectively, against fourth instar larvae of Aedes aegypti. Park et al (2002) reported the compounds retrofractamide A (0.039 ppm), pipercide (0.1 ppm), guineensine (0.89 ppm), pellitorine (0.92 ppm) and piperine (5.1 ppm) derived from the fruits of Piper nigrum against A. aegypti third instar larvae.…”
Section: Resultsmentioning
confidence: 96%